PENGARUH LATIHAN DEPTH JUMP TERHADAP POWER OTOT TUNGKAI PADA TIM BOLA VOLI PUTRA SMPN 1 MANDAU - Heriyandi, Tri; Slamet, Slamet; Sulastio, Agus (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
The problem in this research is that when striking the ball it seems less like jumping. And when jumping is often not optimal due to weak leg muscle strength, the opponents are easily looking for points when the conditions in the Male Volleyball Team 1 are Mandau. The title of this research is